Crystal structure of tert-butyl (1S,2R,5R)-2-(hydroxymethyl)-4-(4-methoxyphenyl)-6-oxa-3-azabicyclo[3.1.0]hexane-3-carboxylate, C17H23NO5 - Caracelli, Ignez; Zukerman-Schpector, Julio; Garcia, Ariel L. L.; Correia, Carlos Roque D.; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C17H23NO5, monoclinic, P21 (no. 4), a = 6.0479(9) Å, b = 9.7032(10) Å, c = 14.711(2) Å, β = 94.174(9)°, V = 861.0(2) Å3, Z = 2, Rgt(F) = 0.0440, wRref(F2) = 0.1436, T = 293(2) K.